Analisis Kemampuan Pemecahan Masalah Matematika Setelah Pembelajaran dengan Pendekatan MEAs pada Materi Sistem Persamaan Linier Tiga Variabel - Hanifa Zulfitri; Nyimas Aisyah; Indaryanti Indaryanti (Jurnal Gantang, 2019)
Abstract This research is a qualitative descriptive research that aims to investigate the mathematical problem solving after learning with MEAs on linier equation system of three variables. The subject of this research are 5 students of X class of MIA 6 SMA Negeri 10 Palembang. The data of this study was collected by three item of problem solving test on SPLTV and an interview to obtain the data deeply. The result of this study show that the indicator of problem solving that the most often appear is indicator of understanding the probelm,where this indicator appears at each level of ability of students, namely high, medium, and low. While indicator that are very rare to appear are indicator looking back. Where this indicator only appears at the level of the ability of students is high, while for the the level of ability of students who are moderate and low this indicator does not appear. The cause of this indicator rarely arises because most students ignore the command to look back, students feel enough to get the final results without re-analyzing the results that have been obtained. Keywords: Analysis, Model Eliciting Activities, Problem Solving